Leishmania infantum mimotopes and a phage–ELISA assay as tools for a sensitive and specific serodiagnosis of human visceral leishmaniasis - Salles, Beatriz C.S.; Costa, Lourena E.; Alves, Patrícia T.; Dias, Ana C.S.; Vaz, Emília R.; Menezes-Souza, Daniel; Ramos, Fernanda F.; Duarte, Mariana C.; Roatt, Bruno M.; Chávez-Fumagalli, Miguel A.; Tavares, Carlos A.P.; Gonçalves, Denise U.; et al. (Diagnostic microbiology and infectious disease, 2017)
Serological methods used to diagnose visceral leishmaniasis (VL) are considered minimally invasive, but they present problems related with their sensitivity and/or specificity. In this study, a subtractive selection using the phage display technology against antibodies from healthy subjects living in endemic and non-endemic areas of disease, as well as from Chagas disease patients and those developing active VL, was developed. The aim of this study was to select bacteriophage-fused epitopes to be used in the serodiagnosis of human VL. Eight phage clones were selected after the bio-panning rounds, and their reactivity was evaluated in a phage-ELISA assay against a human serological panel. A wild-type clone and the recombinant K39-based immunochromatographic test were used as controls. In the results, it was shown that all clones showed an excellent performance to serologically identify VL patients, demonstrating the feasibility of the isolated phages for developing a specific and sensitive serodiagnosis of human VL. [Display omitted] •A subtractive phage display selection was performed.•Eight Leishmania infantum specific mimotopes were selected.•Phage clones expressing these mimotopes were amplified.•Phages were evaluated for the serodiagnosis of human visceral leishmaniasis.•They showed high sensitivity and specificity values in a phage-ELISA assay.